On Lu Yao's Life in Feminist Perspective: Confucian Traditions and (Asian Journal of Social Science Studies, 2022)
Lu Yao's Life is a complex system of emotional weaving, with intricate character relationships, multiple and diverse changes in characters' feelings, multiple contradictions intertwined, power discourses constantly intervening, male absolutes highlighted everywhere, women's low status even pathetic, and implicit gender issues constantly thrown out to readers unintentionally and intentionally, but mixed with external whitewashing factors. The author tries to use feminist criticism to expose the ugly portrayal of men in Life, to reveal the implicit devaluation of women, and to restore the ecology of gender portrayal itself.